Islam on civilization, humanism & knowledge - Omer, Spahic (Dar al-Wahi Publication, 2023)
This book deals with the triad of civilization, humanism and knowledge from the perspectives of both the Islamic and Western worldviews. Some of the issues discussed are as follows: the problematic origins and objectives of the concept of civilization; a mission to colonize in the name of civilization; Islamic alternatives for the flawed concept of civilization; the inappropriateness of the Greco-Roman and Renaissance traditions of humanism as the foundation of the modern Western civilization; the meaning of humanism in Islam and how such a philosophy was instrumental in outlawing the representation of man in art; the meaning of true knowledge; the sanctity of knowledge and knowledge-seeking in Islam; Islam as a religion based on knowledge; the battle of Badr as a miracle and the battle of Uhud as a reality check; the validity of Socrates’ inquiry method and whether Socrates was a prophet; how Muslims should approach history; and the relationship between faith, knowledge and social involvement. The book aims to shed light on the foundational premises of the prospect of dialogue among civilizations and even religious pluralism; to lend support to calls for revisiting - yet demystifying - some of the critical chapters in history, correcting them as much as possible and then moving forward; and to enrich discourses on integration as well as Islamization of knowledge. Needless to say that educational systems, supported by diverse socio-political agendas, are most responsible for the status quo. They endorse and perpetuate myriads of historical, together with civilizational, not only half-truths, but also utter fabrications. The blatant truth is rarely the aim. It is seldom coveted for its own sake, most of the time being manipulated or subjected to the vicissitudes of other designs. Instead of being ends in themselves, the historical and civilizational verities have been turned into a means to someone’s or something’s own ends. As far as Islam and Muslims are concerned, acknowledging and living the truth is humankind’s raison d’etre. That truth is presented to man by way of the revelation, and the fulfillment of man’s noble vicegerency mission on earth is predicated but by the recognition and implementation of that truth. The importance of the subjects of civilization (authentically meaningful, dynamic and productive life paradigms), humanism (authentic optimization of the potential and agency of human beings), and knowledge (prerequisite as well as medium for both civilization and humanism) is paramount in affirming the truth. So much so that the three could be perceived as the truth’s siblings. Only through them the grandeur of the truth can be displayed – and appreciated. Which is why Islam as a comprehensive religion and a way of life was always in the forefront of ensuring the genuine happiness of man, via ensuring his physical, spiritual and mental wellbeing, and was at the same time committed to removing the obstacles that could hinder humanity’s progress towards self and collective actualization. Distorting the realms of civilization, humanism and knowledge – partly or substantially - Islam sees as an existential crime against the humanness of man, the nobility of life, and the inviolability of the truth. The culprits are to be held accountable, while the genuinely enlightened servants of the truth are to work tirelessly on mending the situation. This book wishes to bring home to its readers the consequentiality of these concerns.